Dual Role of Lysophosphatidic Acid Receptor 2 (LPA2) in Amyotrophic Lateral Sclerosis - Puigdomenech-Poch, Maria; Martínez-Muriana, Anna; Andrés-Benito, Pol; Ferrer, Isidre; Chun, Jerold; López-Vales, Rubèn (Frontiers in Cellular Neuroscience, 2021)
Lysophosphatidic acid (LPA) is a pleiotropic extracellular lipid mediator with many physiological functions that signals through 6 known G protein-coupled receptors (LPA1-6). In the central nervous system (CNS), LPA mediates a wide range of effects including neural progenitor cell physiology, neuronal cell death, axonal retraction, and inflammation. Since inflammation is a hallmark of most neurological conditions, we hypothesized that LPA could be involved in the physiopathology of amyotrophic lateral sclerosis (ALS). We found that LPA2 RNA was upregulated in post-mortem spinal cord samples of ALS patients and in sciatic nerve and skeletal muscle of SOD1G93A mouse, the most widely used ALS mouse model. To assess the contribution of LPA2 to ALS, we generated a SOD1G93A mouse that was deficient in Lpar2. This animal revealed that LPA2 signaling accelerates disease onset and neurological decline but, unexpectedly, extended lifespan. To gain insights into the early harmful actions of LPA2 in ALS, we studied the effects of this receptor in the spinal cord, peripheral nerve and skeletal muscle of ALS mice. We found that LPA2 did not contribute to motoneuron death, microgliosis, astrogliosis, or degeneration and demyelination of motor axons. However, we observed that Lpar2 deficiency protected against muscle atrophy. Moreover, we also found the deletion of Lpar2 reduced the invasion of macrophages into the skeletal muscle of SOD1G93A mice, linking LPA2 signaling with muscle inflammation and atrophy in ALS. Overall, these results suggest for the first time a dual contribution of LPA2 to ALS, first accelerating the disease, and then, extending survival.